A novel cactus-like Fe3O4/Halloysite nanocomposite for arsenite and arsenate removal from water. (1st July 2019) - Song, Xiaoli; Zhou, Lei; Zhang, Yun; Chen, Pei; Yang, Zhenglong
Abstract: In this paper, Fe3 O4 was loaded on the surface of halloysite nanotubes (HNTs) by a simple one-pot coprecipitation method to prepare Fe3 O4 /HNTs nanocomposites (Fe3 O4 /HNTs) for arsenic removal from water. The growth mechanism and the arsenic removal performance of the nanocomposites were investigated. The morphology of Fe3 O4 /HNTs varied as the mass ratio of the total iron salts (Fe 3+ : Fe 2+ = 2:1) to HNTs changed. A novel cactus-like Fe3 O4 /HNTs was obtained when the ratio is 3:1. The removal efficiency of arsenite (As (III)) and arsenate (As (V)) by the cactus-like Fe3 O4 /HNTs could reach 98.56% and 99.62%, respectively. Much more, the removal efficiency of As (III) of the cactus-like Fe3 O4 /HNTs is higher than that of most of the other materials reported under the same conditions. In addition, the cactus-like Fe3 O4 /HNTs showed good reusability, with an arsenic removal efficiency of up to 83.36% after 6 times of reuse. Adsorption kinetics and isothermal adsorption studies have shown that adsorption is a chemical process with a maximum adsorption capacity of 408.71 mg As(III)/g and 427.72 mg As(V)/g, respectively. The facile preparation method, excellent arsenic removal performance and reusability make the cactus-like Fe3 O4 /HNTs a potential adsorbent for sustainable arsenic removal from contaminated water. Graphical abstract: Image 1 Highlights: A novel cactus-like Fe3 O4 /HNTs magnetic nanocomposite was prepared for arsenic removal. Fe3 O4 /HNTs showed high removal efficiency for both trivalent and pentavalent arsenic. Fe3 O4 /HNTs showed great reproducibility.